# manipulating convergent series

###### Theorem 1.

If the series  $a_{1}+a_{2}+\cdots$  and  $b_{1}+b_{2}+\cdots$converge and have the sums $a$ and $b$, respectively, then also the series

 $\displaystyle(a_{1}+b_{1})+(a_{2}+b_{2})+\cdots$ (1)

converges and has the sum $a\!+\!b$.

Proof.  The $n^{\mathrm{th}}$ partial sum of (1) has the limit

 $\lim_{n\to\infty}\sum_{j=1}^{n}(a_{j}+b_{j})=\lim_{n\to\infty}\sum_{j=1}^{n}a_% {j}+\lim_{n\to\infty}\sum_{j=1}^{n}b_{j}=a\!+\!b.$
###### Theorem 2.

If the series  $a_{1}+a_{2}+\cdots$  converges having the sum $a$ and if $c$ is any , then also the series

 $\displaystyle ca_{1}+ca_{2}+\cdots$ (2)

converges and has the sum $ca$.

Proof.  The $n^{\mathrm{th}}$ partial sum of (2) has the limit

 $\lim_{n\to\infty}\sum_{j=1}^{n}ca_{j}=c\lim_{n\to\infty}\sum_{j=1}^{n}a_{j}=ca.$
###### Theorem 3.

If the of any converging series

 $\displaystyle a_{1}+a_{2}+a_{3}+\cdots$ (3)

are grouped arbitrarily without changing their , then the resulting series

 $\displaystyle(a_{1}+\cdots+a_{m_{1}})+(a_{m_{1}+1}+\cdots+a_{m_{2}})+(a_{m_{2}% +1}+\cdots+a_{m_{3}})+\cdots$ (4)

also converges and its sum equals to the sum of (3).

Proof.  Since all the partial sums of (4) are simultaneously partial sums of (3), they have as limit the sum of the series (3).

Title manipulating convergent series ManipulatingConvergentSeries 2013-03-22 14:50:49 2013-03-22 14:50:49 pahio (2872) pahio (2872) 12 pahio (2872) Theorem msc 40A05 msc 26A06 SumOfSeries MultiplicationOfSeries